Double-crown-retained removable dental prostheses: a retrospective study of survival and complications - Schwindling, Franz Sebastian; Dittmann, Britta; Rammelsberg, Peter (The journal of prosthetic dentistry, 2014)
STATEMENT OF PROBLEM: Research data are scarce on double-crown-retained removable dental prostheses. In double-crown-retained removable dental prostheses, crown-like copings are definitively cemented to the abutment teeth and serve as prosthesis attachments. - PURPOSE: The purpose of this study was to evaluate the survival of double-crown-retained removable dental prostheses in use for 7 years and to determine their most common complications. - MATERIAL AND METHODS: A retrospective analysis was conducted to investigate the clinical outcome of 117 prostheses in 86 patients with 385 abutment teeth. Thirty-two telescopic-crown-retained removable dental prostheses, 51 conical-crown-retained removable dental prostheses, and 34 resilient telescopic-crown-retained overdentures were clinically reexamined by 1 investigator. Prosthesis success was defined as survival without severe complications (abutment tooth extraction). Statistical analyses were performed with Kaplan-Meier modeling and Cox regression (α=.05). - RESULTS: Minor complications, for example, the decementation of primary crowns (34.2%), failure of the veneer of secondary crowns (11.1%), fracture of the denture base (17.1%), and the need for relining (12%), were common. Cumulative prosthesis survival for all types of prostheses was 93.8% after 7 years. After the same period, prosthesis success was 90% for telescopic-crown-retained removable dental prostheses and 78.5% for conical-crown-retained removable dental prostheses and resilient telescopic-crown-retained overdentures. - CONCLUSIONS: The medium-term double-crown-retained removable dental prosthesis survival found in this retrospective investigation appears acceptable. When bearing in mind the limits of this study, this kind of prosthesis might be a viable treatment option for patients with a reduced dentition. However, more laboratory and clinical research is necessary to reduce the incidence of minor complications and confirm the present in vivo results in larger patient groups.